Synchronous breast carcinoma (with Paget’s disease) and renal cell carcinoma with tubercular axillary lymphadenitis: a rare presentation - Ranganath, Sonika; Kasliwal, Navin Rajendra; Shah, Aruna Karad; Maydeo, Rohan Amit (International Surgery Journal, 2021)
Synchronous malignancy are defined as two primary malignancy of two different organs occurring concurrently or within 6 months duration. Reports of synchronous breast carcinoma with RCC (renal cell carcinoma) are very limited. We presented here the first case of non-metastatic synchronous RCC with breast carcinoma and Paget’s disease associated with tubercular axillary lymphadenitis in a 62 year old female for which she underwent right MRM and right partial nephrectomy. She received chemotherapy and anti-tubercular therapy post-surgery and currently on oral hormonal therapy. Follow up scans showed stable disease. There have been cases of breast cancer with TB lymphadenitis as well as of double synchronous malignancies involving breast carcinoma and RCC. Most of the multiple malignancies reported in literature are metastatic tumours or metachronous breast malignancy with RCC. A case of synchronous primary ca breast with pages disease coexisting with primary RCC along with tubercular lymphadenopathy is yet to be reported in literature. This might just be the first one.